2023
DOI: 10.7759/cureus.38568
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Inhibitory Effect of Lactobacillus rhamnosus on Halitosis-Causing Bacteria: An Invitro Microbiological Study

Abstract: Aim: To determine the effectiveness of Lactobacillus rhamnosus in inhibiting halitosis-causing bacteria relative to other possible inhibitors, such as mouthwashes. Materials and Methods: This in vitro study was done using a diffusion test with three groups with 11 samples in each group: group A, Porphyromonas gingivalis ; group B, Tannerella forsythia ; and group C, Prevotella intermedia . At 24, 48, and 72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study revealed that for individuals with halitosis, the eight-week intake of this oral probiotic could serve as a beneficial intervention to reduce bad breath and enhance oral health-related quality of life (Lee et al, 2020). Patil (Patil et al, 2023). In another recent randomized, double-blinded study, Han and colleagues aimed to explore the effects of tablets containing W. cibaria on halitosis.…”
Section: Probiotics In Halitosismentioning
confidence: 99%
“…The study revealed that for individuals with halitosis, the eight-week intake of this oral probiotic could serve as a beneficial intervention to reduce bad breath and enhance oral health-related quality of life (Lee et al, 2020). Patil (Patil et al, 2023). In another recent randomized, double-blinded study, Han and colleagues aimed to explore the effects of tablets containing W. cibaria on halitosis.…”
Section: Probiotics In Halitosismentioning
confidence: 99%